THE EFFECT OF COMPANIES’ ETHICAL COMMITMENTS ON FINANCIAL PERFORMANCE : THE MODERATING EFFECT OF OWNERSHIP STRUCTURE - Zahrina Ghassani Amalina; Agung Juliarto (Diponegoro Journal of Accounting, 2021)
Business ethics began to receive special attention in 2001 after the emergence of the Enron case scandal, where there was a ethic violation . The percentage of corruption cases continues to increase every year until 2020. There is also a corruption case at PT Asuransi Jiwasraya resulting in huge state losses alleged corruption case. Corruption, bribery, and money laundering is unethical behavior. The application of corporate ethic commitment such as company values, code of ethics, whistleblowing policies, and ethics committe are expected to affect company financial performance. In addition, shareholders one of the parties that haves important roles and are affected by the company's performance. So this research is conducted to investigate the effect of ethical commitment on financial performance measured using Return on Asset (ROA), and the moderating effect of ownership structure.The population in this study consisted of all sectors of listed companies on the main board of the Indonesian stock exchange 2018-2019. The sample was companies included in SWA 100 Best Wealth Creators category resulting in 68 observations for analysis. This study used Ethical Commitment Item (ECI) to measure companies’ ethical commitment and moderated regression analysis for hypothesis testing.The results of this study indicate that disclosure of company ethical commitment has a significant effect on financial performance measured by using ROA. Furthemore, the public ownership does not moderate the relationship between ethical commitment on financial performance measured by using ROA.